The Concept of Balanced Human Beings - Rohana, Hamzah; Haslinda, Hashim; Nurul Izzati, Atan; Sarimah, Ismail (worldconferences.net, 2016)
The education system in Malaysia is based on a philosophy that emphasizes to produce balance and harmony human being. This idea should be the main agenda in all levels of education. However, as time goes by, the idea becomes vague and poorly understood especially by the younger generation of educators. Therefore, this study aims to regain explanation from experts in education about the concept of balanced human beings. The design of this study is a qualitative study. Nine experts in education have been selected using purposive and snowball sampling technique. The information obtained from the interviews has been analyzed using coding system to create themes for each research question. Results of the study found that the experts’ define the concept of balance human being as a person with strong belief and faith to God, good relationship with others and develop well in all human potentials in an integrated manner and knowledgeable. Thus, the real purpose of education is to inculcate the value of belief and faith to God throughout all intellectual subjects and this method is known as integrated approach in education. Therefore integrated approach in education is the answer to produce integrated thinker and balanced human beings through education system.